Critical Thinking Skills: Improvement Through Learning Ownership-PBL Approach on Students - Listyorini, Dwi; Prabaningtyas, Sitoresmi; Mustakim, Siti Salina; Risqillah, Ulfa (Jurnal Pendidikan Sains, 2025)
Through a method called "Learning Ownership," students actively participate in the educational process and comprehend the context, objectives, and applications of the content they have learned. A learner can customize each educational encounter to align with their present and future learning goals once they have control over their learning processes. The skills and practices required for ownership are highly versatile and applicable in various educational environments. The aim of this study was to unveil the effect of the learning ownership-PBL model on students' critical thinking skills. The sampling technique used in this research was random sampling, which consisted of 2 groups: the control group used the PBL model, and the experimental group used the learning ownership-PBL model. For the learning ownership parameter, we use a questionnaire consisting of 33 questions, and for the critical thinking parameter, we use an essay consisting of 5 questions. The test used is an independent sample T-test and Spearman test to see the correlation between learning ownership and critical thinking skills. The study found that students in the experimental group improved their learning ownership and critical thinking scores more than students in the PBL model alone in every way. Learning ownership (PBL) strongly correlated and significantly increased students' critical thinking skills. Thus, we conclude that learning ownership-PBL can increase student critical thinking skills. DOI: https://doi.org/10.17977/jps.v13i12025p001